Risk Factors for Lower Extremity Amputation in Diabetic Foot Ulcer Patients: A Case-Control Study - Gusti Agung Ayu Ira Kencana Dewi; Sony Wibisono; I Putu Alit Pawana (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2020)
Introduction: Diabetes mellitus is a metabolic syndrome that is marked by higher blood glucose. The uncontrolled high blood glucose can lead to complication, such as diabetic foot. Diabetic foot is the most reason why diabetic patients are hospitalized. Diabetic foot that cannot heal may lead to lower extremity amputation. The purpose of this study was to describe the risk factors of lower extremity amputation in diabetic foot ulcer patients.Methods: This study used a case-control study of diabetic foot patients in Dr. Soetomo General Hospital from January 2015 to December 2017. This study used the data from medical records in Inpatient Installation Department of Internal Medicine. Patients with diabetic foot ulcer and lower extremity amputation due to diabetes were included in this study. Incomplete medical records were excluded. Data of samples were divided to two groups, i.e. the amputation group and the non-amputation group with a ratio of 1:1. Risk factors of amputation that were analyzed were male, old age, and the history of ulcer/lower extremity amputation.Results: Based on the data of 36 samples, there were 11 male patients (61.1%) and 7 female patients (38.9%) who experienced lower extremity amputation. The average age of amputation group was 59.61 years old with a range of ages from 39 to 72 years old. This study found the risk factors for lower extremity amputation in diabetic foot ulcer patients was the history of ulcer/amputation due to diabetes (OR 5.0, 95% CI 1.065-23.464, p = 0.034). Conclusion: The risk factor for lower extremity amputation in diabetic foot ulcer patients was the history of ulcer/amputation due to diabetes.